Determination of the Excretion of TSH, T3, T4 Hormones in Blood According to the Pulse Index (160) for Female Tennis Players of Kufa University - Nazar Hussein al-Naffakh (Journal of Global Pharma Technology, 2017)
The research included a number of axes focused on these axes on the analysis of the hormones involved in the study and this is by giving a particular effort to raise the pulse to 160 N / d where the pulse is measured after an exercise or effort to raise the pulse of the player and when the completion of exercises The pulse is measured by the player through a device to measure the pulse and when the arrival to the pulse specified blood is drawn to the player and then the analysis of the hormones involved to study at the pulse of the specific measurement and know what changes in these hormones at this pulse and after the analysis in the laboratory allocated and a special device The results are collected Obtained and then deal with these results statistically to extract what extent attributed the changes that have taken place for these hormones for each player. The results showed that there were clear changes in hormone levels at pulse 160 and these changes vary from one player to another.Keywords: Sports Performance, Thyroid hormone analysis (T3, T4), Thyroid stimulating hormone (TSH) and effect of hormones on pulse index (160).